2020
DOI: 10.1177/1120700020904689
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies in the offspring of women with total hip replacement: a nationwide register study in Finland

Abstract: Background: Few previous studies have analysed the possible teratogenic effect of maternal total hip replacement (THR) on congenital anomalies. The aim of this study was to estimate the risk of major congenital anomalies in the offspring of women with THR. Furthermore, we compared the risks based on type of implant (metal-on-metal [MoM]/non-MoM). Methods: The study population for this register-based cohort study was gathered from six Finnish national registers. All fertile-aged females who underwent THR from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…No teratogenic effects on the newborns were observed; yet, no concrete data existed in terms of the children’s later development [ 22 ]. Finally, a study by Kuitunen et al [ 23 ], utilizing data from the Finish nationwide registry based on 2429 women with THA history compared to 7276 women as a reference group, denoted that in the THA group, three (5.9%) out of the total number of IAs were executed owing to suspected fetal defects, while four (1.9%) stillbirths and eight (3.8%) newborns with one or more major abnormalities were noted. Regarding the control group, 13 (5.5%) out of the total number of IAs were performed due to suspected fetal defects, whilst eight (0.6%) stillbirths and 47 (3.3%) newborns with one or more major defects were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No teratogenic effects on the newborns were observed; yet, no concrete data existed in terms of the children’s later development [ 22 ]. Finally, a study by Kuitunen et al [ 23 ], utilizing data from the Finish nationwide registry based on 2429 women with THA history compared to 7276 women as a reference group, denoted that in the THA group, three (5.9%) out of the total number of IAs were executed owing to suspected fetal defects, while four (1.9%) stillbirths and eight (3.8%) newborns with one or more major abnormalities were noted. Regarding the control group, 13 (5.5%) out of the total number of IAs were performed due to suspected fetal defects, whilst eight (0.6%) stillbirths and 47 (3.3%) newborns with one or more major defects were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the control group, 13 (5.5%) out of the total number of IAs were performed due to suspected fetal defects, whilst eight (0.6%) stillbirths and 47 (3.3%) newborns with one or more major defects were recorded. No noteworthy discrepancies were descried in terms of the rates of defects between women who had undergone metal-on-metal THA and those with other types of hip prostheses [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A population-based study in Finland demonstrated that the birth rate was 20% to 60% lower in patients with a THR than in a reference population 38 . The same group demonstrated that, reassuringly, THR did not increase the rate of congenital anomalies in the offspring of women with a THR 39 .…”
Section: The Prosthetic Hip In Pregnancymentioning
confidence: 91%